Fajar Islam di Hijaz: Mengungkap Peran Muhammad SAW. dalam Membentuk Kebudayaan Arab Baru - Ashfa, itasya afiani (Maliki Interdisciplinary Journal, 2025)
This article examines the revolutionary role of Prophet Muhammad (PBUH) in shaping a new Arab culture in the Hijaz region during the 7th century CE. Before the arrival of Islam, Arab society lived within a strong yet fragmented tribal system, marked by jahiliyyah practices that degraded human values. Through his prophetic mission, Prophet Muhammad introduced the teachings of tawhid, establishing the oneness of God while reforming social, political, economic, and cultural structures. These reforms included social justice, women’s rights, the abolition of economic injustice, and the promotion of education and literacy. The Constitution of Medina became an early foundation for a multicultural society based on justice and consultation. This social transformation expanded rapidly, making Islam a major civilization that has influenced global fields such as science, art, architecture, and philosophy. This study emphasizes that civilizational change can emerge from strong spiritual and moral vision, as exemplified by Prophet Muhammad (PBUH) in building the foundations of Islamic civilization.